Engineered Heart Slice Model of Arrhythmogenic Cardiomyopathy Using Plakophilin-2 Mutant Myocytes - Blazeski, Adriana (Tissue Eng Part A, 2019)
Arrhythmogenic cardiomyopathy (AC), a cause of sudden cardiac death among young and otherwise healthy individuals, is a heritable disease that can be modeled in vitro using patient-specific cardiac myocytes (CMs) from induced pluripotent stem cells. An understanding of underlying disease mechanisms, particularly in the early concealed stages, could lead to new diagnosis and treatment strategies. However, multicellular syncytial models are needed to understand how genetically encoded mutations of the desmosomes that interconnect cells lead to aberrant electrical conduction and arrhythmias. In this study, engineered heart slices (EHS) were created by seeding human induced pluripotent stem cell-derived CMs from an AC patient with a plakophilin-2 (PKP2) mutation onto intact slices of decellularized myocardium and then compared to age-matched AC CMs cultured as monolayers. After 2 weeks of culture, EHS developed into a confluent multilayered syncytia that exhibited spontaneous coordinated beating and could be electrically paced at cycle lengths ranging from 2000 to 500 ms. AC CMs cultured as EHS displayed highly aligned, dense, and ordered sarcomeric structures, with gene expression analyses revealing increased maturation. In addition, AC-relevant genes were affected by CM culture in EHS, with a substantial increase in PPARG and a decrease in SCN5A compared to monolayers. Functionally, AC EHS exhibited similar conduction velocities, shorter action potentials, and a slower and steadier spontaneous beat rate compared with monolayers. Reentrant arrhythmias could also be induced in AC EHS by S1-S2 pacing. Our findings suggest that the EHS microenvironment enhances the phenotype of AC CMs in culture while allowing for functional studies of an appropriately aligned syncytium of AC-CMs. Results reported here demonstrate the benefits of studying AC using EHS, a tissue construct that allows syncytial culture and the incorporation of matrix cues. IMPACT STATEMENT: Genetic heart diseases such as arrhythmogenic cardiomyopathy (AC), a common genetic cause of sudden cardiac death, can be modeled using patient-specific induced pluripotent stem cell-derived cardiac myocytes (CMs). However, it is important to culture these cells in a multicellular syncytium with exposure to surrounding matrix cues to create more accurate and robust models of the disease due to the importance of cell–cell and cell–matrix interactions. The engineered heart slice, constructed by seeding CMs on intact decellularized matrix slices, allows molecular and functional studies on an aligned multilayered syncytium of CMs. This study reveals the potential for an improved disease-in-a-dish model of AC.